2005
DOI: 10.1021/la051124y
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Nanotube Film by Filtration as Cathode Catalyst Support for Proton-Exchange Membrane Fuel Cell

Abstract: A simple filtration method is developed to prepare a partially oriented superhydrophobic film of carbon nanotubes (CNTs) that have been catalyzed with uniform small Pt nanoparticles (2.8 nm) at high metal loading (30 wt %). A proton-exchange membrane fuel cell with the oriented CNT film as the cathode achieves higher single-cell performance than those with carbon black and a disordered CNT-film-based cathode probably because of the enhanced electrocatalytic activity of Pt/CNT and improved mass transport within… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
150
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 214 publications
(152 citation statements)
references
References 17 publications
2
150
0
Order By: Relevance
“…Most of the parameters used in the model validation are obtained from Li et al [18], who reported the measured cell performance data having an ordered nanostructured CCL. Since the present model predicts an ordered nanostructured CCL performance, to compare with the measured cell performance, the membrane ohmic overpotential is accounted using an expression presented by Baschuk and Li [56]:…”
Section: Model Validationmentioning
confidence: 99%
See 4 more Smart Citations
“…Most of the parameters used in the model validation are obtained from Li et al [18], who reported the measured cell performance data having an ordered nanostructured CCL. Since the present model predicts an ordered nanostructured CCL performance, to compare with the measured cell performance, the membrane ohmic overpotential is accounted using an expression presented by Baschuk and Li [56]:…”
Section: Model Validationmentioning
confidence: 99%
“…5 shows the comparison between the predicted and measured cell performance having an ordered nanostructured CCL. The lines represent the model predictions, while the symbol represents the measured cell performance data obtained from Li et al [18]. The solid line represents the predicted ordered nanostructured CCL performance at 343 K and 2 atm.…”
Section: Model Validationmentioning
confidence: 99%
See 3 more Smart Citations